Seamount ophiuroids from the High Seas of the western Indian Ocean - O’hara, Timothy D.; Thuy, Ben (Zootaxa, 2025)
Twelve new species of Ophiuroid (brittle stars) are described, using both morphological and DNA evidence, from four seamounts (Atlantis, Melville, Coral and Walters Shoal) in the Area Beyond National Jurisdiction (High Seas) of the SW Indian Ocean, one in each of the genera: Ophiocreas (Euryalidae), Ophiopyrgus, Amphiophiura, Glaciacantha, Ophiuroglypha, Stegophiura (Ophiopyrgidae), Ophiectodia, Ophiosabine, Ophiacantha, Ophiolimna (Ophiacanthidae), Ophiomyxa (Ophiomyxidae) and Ophionereis (Ophionereididae). In addition, we resurrect several synonymised genus and species-level taxa, including the genera Ophiopyrgoides for a clade of Ophiopyrgus that includes O. trispinosus (type), O. saccharatus, and O. depressus; Ophiectodia for the clade containing Ophiacantha enopla (type), O. imago and O. opulenta; Ophiodiplax for Ophiacantha antarctica, and the subgenus Ophiotriton for the Ophionereis species O. semoni (type), O. dubia, O. amoyensis, O. andamanensis, O. hexactis, O. intermedia, O. thryptica, O. tigris, O. vivipara and O. sexradia. Resurrected species include: Astrothamnus papillatus and Gorgonocephalus pectinatus from South Africa; and Ophiomyces peresi for North Atlantic/Mediterranean specimens of O. grandis, and Ophiotreta rufescens for North Atlantic specimens of O. valenciennesi. The following species are transferred to different genera: Asterostegus (Astroceras spinigerum); Ophiocreas (Asteroschema lissum); Ophiopyrgus (Amphiophiura solida, A. latro, A. bakeri, A. liberata and A. spatulifera); Ophiomastus (O. biocal); Glaciacantha (Ophiocten cryptum and O. banzarei); Stegophiura (Amphiophiura lapidaria); and Amphiophiura (Stegophiura sculpta, S. vivipara, Ophioplinthus inflatus). Finally, we make two species-level synonymies: Amphiophiura pertusa is synonymised with Ophiopyrgus latro and Ophiacantha veterna with Opiectodia enopla. The biogeography of the fauna of each seamount depends on the location and summit depth. The remote Atlantis Seamount has a widespread bathyal seamount fauna, Coral Seamount has a temperate Southern Ocean bathyal fauna, and Walters Shoal has a continental SE African/Madagascar shelf and upper bathyal fauna, and a mixed temperate/tropical Indo-Pacific mid-bathyal fauna.